OPERATING EXPENSES PORTFOLIO PRIORITIZATION BY USING SIMPLE MULTI-ATTRIBUTE RATING TECHNIQUE (SMART) AND ANALYTIC HIERARCY PROCESS (AHP) METHOD (CASE STUDY: PT. PETROLEUM CENTRAL INDONESIA) - Sandryastuti, Irani
With the end of RKN Block PSC in 2021, PCI is expected to optimize its cost by maintaining lower Non-Fuel Lifting cost of oil production. Operations & Maintenance (O&M) as one of the core group in PCI has responsibilities to deliver oil production as per business plan target with minimum OPEX. Other than activities to gain oil production, PCI is also dealt with some mandatory obligation namely personal and process safety compliance, environmental and government regulations compliance. Prioritization and selecting the projects, programs or activities, programs in O&M is one of the cost optimization strategies that can do in the budgetary planning phase. Currently, there is no predefined prioritization model to prioritize the OPEX portfolio and what criteria that are agreed in the decision-making process to prioritize the OPEX portfolio. In this research, 2 methods of Decision-Making process are used. Those are Simple Multi-Attribute Rating Technique (SMART) method and Analytic Hierarchy Process (AHP) method. The SMART method is used to develop prioritization list in a high-level portfolio of O&M OPEX. The high-level portfolio is developed based on the program summary proposed yearly in the WP&B to SKKMIGAS. While the AHP method combined with SMART approach is used to develop the prioritization model for sub activities under high-level portfolio. In SMART method for developing the high-level O&M OPEX Prioritization List, the Focus Group Discussion (FGD) is done to define the attributes that need to be considered namely cost, personal safety, process safety, environmental compliance, asset integrity, and production impact. Based on benefit analysis, from 25 activities the first rank of the high-level O&M OPEX prioritization is the Process Safety Management (PSM) program. While at the bottom rank is idling activities. To obtain provisional decision, trading cost against benefit analysis is done. This is conducted to see which alternative can provide the maximum benefit but with least total cost. AHP method combined with the SMART approach is used to develop prioritization model in the sub-activities. The AHP method define the weight factor of criteria and sub criteria, while the SMART approach with direct rating measurement will scale the alternatives to rank the decision alternatives or sub-activities and prioritize the from the highest to the lowest rank. To develop the criteria and sub criteria with the weight factor, 2 (two) consecutive surveys are conducted. The first survey is the initial criteria survey and the second survey is the pairwise comparison survey. The analysis generates 5 criteria and 12 sub criteria that will be used in the AHP hierarchy structure. The final criteria for this prioritization are Financial, Technical, Safety, Compliance and Environmental. While the sub criteria for this prioritization are : Production impact, LPO, Ratio cost to benefit, Reliability, Efficiency, Personal safety, Process safety, Government regulations, Company guidelines, Zero water discharge, Oil spill prevention, and Air gas emission. The pairwise comparison of the main criteria put Safety become the most importance criteria compare to other criteria by resulting the highest weight factor of 0.440, while the next criteria that become more important is Compliance with weight factor of 0.284 and continue with Environmental criteria with weight factor of 0.189. The other 2 criteria Financial and Technical become less important to other with resulting similar weight factor only 0.048 and 0.040. For sub criteria, the pairwise comparison produce global weight factor of each sub criteria where Personal safety has the largest global weight of 0.310. Second sub criteria is Government regulations with 0.221 weight and the third is Process safety with 0.129 weight. The sub criteria at the bottom rank is LPO with weight 0.008. Using mathematical programming problem solution trough Solver Tool in Microsoft Excel, the analysis to select activities in OPEX Portfolio by maximizing the total benefits in certain budget limitation is conducted.